Comportamento dos consumidores da Região Sul do Brasil em relação ao queijo colonial artesanal - Dannebrock, Jonathan Renan (2022)
Brazil is a major consumer and producer of cheese, especially in southern Brazil. In the South region, production and consumption is concentrated in the Colonial type, which is widely accepted for historical and cultural reasons. Colonial cheese can be industrialized or produced by artisanal processes from small rural producers, who use this activity with the objective of increasing income. In view of the large consumption of cheeses in the southern region of Brazil, this study analyzed the reasons for consumption, acceptance, preference and consumer behavior regarding the characteristics of artisanal Colonial cheese. The research was carried out through questionnaires applied electronically, via Google Forms and data processing was performed with the help of Excell® software and the XL-STAT extension. It was identified that the frequency of consumption of Colonial cheese for the analyzed region is at least 4 to 5 times a week, in which the age group and the state of residence are determining factors for its consumption. The characteristics explored of artisanal Colonial cheese were related to color, shape, flavor, texture, visual appearance when cut and product maturation time, where it was found that Southerners prefer cheese with a medium maturation, light yellow color, round shape, presenting a flavor smooth and smooth texture. Another point addressed in the study was the perception of consumers in relation to the holes and the presence of mold in artisanal Colonial cheese. It was found that the holes are appreciated by the population of southern Brazil, being seen as an attribute that indicates more flavor, a product made in an artisanal way and of good quality. For molds, it was noted that consumers have different perceptions, and they understand dark mold as a sign of contamination and a normal situation to occur, while white mold is seen as a possible and normal situation to occur in artisanal Colonial cheeses and that it's okay to consume. This study allows producers to define better strategies for acting in the market, contributing to the appreciation of artisanal Colonial cheese.